The social construction of the historic center of Liberia, Costa Rica - Chang-Albizurez, Dominique (2025)
Despite its designation as the country’s first historic center—delimited by municipal decree and supported by the local community—Liberia has made limited progress in its preservation and development. Through the extension project “The Social Construction of the Historic Center of the City of Liberia: An Input for Its Sustainable Management,” the Public University, in collaboration with the Municipality of Liberia, the Association for the Culture of Liberia, and the broader community, has employed a participatory methodology to collectively formulate a comprehensive vision for the Historic Center. This initiative seeks to safeguard Liberia’s cultural heritage, including its distinctive earthen architecture and historical traditions, while honoring its role since the eighteenth century as a hub for cultural exchange and a crossroads of diverse influences. This article presents the methodological process, grounded in Participatory Action Research (PAR), and its key outcomes: a co-created vision and general management guidelines structured across four dimensions. Additionally, it critically reflects on the complexities of participatory approaches, highlighting the challenges, barriers, and often-overlooked narratives that emerge beyond conventional frameworks of cultural heritage conservation.